Darier-White disease in siblings responding to isotretinoin - Ramesh M Bhat; Krithi Raviraj Ullal; Anita Caroline Pinto; D Sukumar (Indian Dermatology Online Journal, 2010)
Darier-White disease (keratosis follicularis) is a rare disorder of keratinization involving the epidermis, mucous membranes, and nails. It is said to occur as a result of mutation in the ATP2A2 gene located on chromosome 12q23-24.1. In this article we present the case of two brothers with exacerbations of Darier-White disease who responded very well to systemic retinoids without any side effects within 2 weeks of commencing treatment.